Effects of Clay and Moisture Content on Direct Shear Tests for Clay-Sand Mixtures - Muawia A. Dafalla (Advances in Materials Science and Engineering)
The direct shear test using shear box is commonly recommended by practicing geotechnical engineers to obtain the cohesion and angle of internal friction for granular soils. The clay liners involve sand as a main constituent with added clay of variable proportions. This research aims at investigating the reliability of using the direct shear test for different clay contents and different moisture contents using an adequate shearing strain. These factors were found to affect the bilinear trends of shear force versus horizontal displacement profile as well as vertical displacement versus horizontal displacement curves. The cohesion of the mixture was found to increase consistently with the increase of clay content. Increase in moisture content was found to cause a drop in both cohesion and angle of internal friction. These changes are not independent of the density state of clay-sand mixtures. Standard compaction properties for a range of clay-sand mixtures were investigated. This work provides the general trends expected in direct shear tests for clay-sand mixtures of variable clay and moisture contents.